2006
DOI: 10.1111/j.1365-2958.2006.05209.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal carnitine acetyl transferase is required for elaboration of penetration hyphae during plant infection by Magnaporthe grisea

Abstract: SummaryMagnaporthe grisea, the causal agent of rice blast disease, invades plant tissue due to the action of specialized infection structures called appressoria, which are used to breach the leaf cuticle and allow development of intracellular, infectious hyphae. In this report we demonstrate that peroxisomal carnitine acetyl transferase (CAT) activity is necessary for appressorium function, and in particular, for the elaboration of primary penetration hyphae. The major CAT activity in M. grisea is encoded by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 57 publications
4
121
0
1
Order By: Relevance
“…Defects in ␤-oxidation compromise virulence in phytopathogenic fungi (2,31,32,61,81; see also the accompanying article by Kretschmer et al [33a]). For example, we previously demonstrated that a mutant lacking the multifunctional enzyme Mfe2 in the basidiomycete Ustilago maydis had reduced virulence and sporulation on maize (32).…”
Section: Resultsmentioning
confidence: 99%
“…Defects in ␤-oxidation compromise virulence in phytopathogenic fungi (2,31,32,61,81; see also the accompanying article by Kretschmer et al [33a]). For example, we previously demonstrated that a mutant lacking the multifunctional enzyme Mfe2 in the basidiomycete Ustilago maydis had reduced virulence and sporulation on maize (32).…”
Section: Resultsmentioning
confidence: 99%
“…Fungal growth and conidiation were observed after incubation for 2 to 3 d. For staining with DAB (Sigma-Aldrich), rice leaf sheath samples were incubated in 1 mg/mL DAB solution, pH 3.8, for 8 h and destained with ethanol/acetic acid (94/4, v/v) for 1 h before examination. For aniline blue staining (Bhambra et al, 2006), barley leaves were sampled 72 h after inoculation and incubated in 1 M KOH at 708C for 20 min. After washing three times with water and once with 67 mM K 2 HPO 4 , pH 9.0, the samples were stained with 0.05% aniline blue and examined with a Nikon epifluorescence microscope.…”
Section: Appressorium Formation and Plant Infection Assaysmentioning
confidence: 99%
“…Deletion of pex6 in the fungus Colletotrichum lagenarium reduces disease on bean leaves by impairing appressorium function during the initial stages of infection (36). Recently, a PEX6 homolog and a peroxisome-targeted acetyltransferase have been shown to be required for appressorium formation and pathogenicity of the major rice pathogen Magnaporthe grisea (4,60). Similarly, hex1 mutations impair appressorium formation in M. grisea (68).…”
mentioning
confidence: 99%